2018
DOI: 10.1007/s00330-018-5888-y
|View full text |Cite
|
Sign up to set email alerts
|

Time-series hyperpolarized xenon-129 MRI of lobar lung ventilation of COPD in comparison to V/Q-SPECT/CT and CT

Abstract: Purpose To derive lobar ventilation in patients with chronic obstructive pulmonary disease (COPD) using a rapid time-series hyperpolarized xenon-129 (HPX) magnetic resonance imaging (MRI) technique and compare this to ventilation/perfusion single-photon emission computed tomography (V/Q-SPECT), correlating the results with high-resolution computed tomography (CT) and pulmonary function tests (PFTs). Materials and methods Twelve COPD subjects (GOLD stages I–IV) participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…In this study, adjustment for the variation in the local oxygen concentration was not included in the analysis. T1 may vary between 26 to 33 seconds between different ROIs of the same participant, as we discussed in our previous work [28]. Considering the time delay was calculated over a time period of around 10 seconds, this T1 variation might result in up to 10% variation in signal-time product difference and/or time delay.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, adjustment for the variation in the local oxygen concentration was not included in the analysis. T1 may vary between 26 to 33 seconds between different ROIs of the same participant, as we discussed in our previous work [28]. Considering the time delay was calculated over a time period of around 10 seconds, this T1 variation might result in up to 10% variation in signal-time product difference and/or time delay.…”
Section: Discussionmentioning
confidence: 92%
“…Both gases, at the imaging doses prescribed, are well-tolerated by both healthy individuals and patients with lung diseases [23][24][25]. More recently, hyperpolarised 129 Xe has been shown to be a promising tool for measuring lobar ventilation [26,27], and for identifying temporal changes in the arrival of xenon gas to different parts of the lung [28,29].…”
mentioning
confidence: 99%
“…Exploiting these signals for diagnostic imaging purposes can be difficult since for example, only about 2% of inhaled xenon dissolves into the tissue barrier and RBC [76,79], and the corresponding T 2 * values are often short ($2 ms) [80]. There is an urgent need for efficient short-TE methods to acquire these short T 2 * signals and enable deeper study of a number of lung abnormalities such as ventilation/perfusion mismatch [81,82] and of other organs including xenon brain perfusion imaging [72,83] and imaging of the xenon-encapsulated Cryptophane-A functionalized with anti-cancer drugs [84].…”
Section: Dissolved Phase 129 Xe Mrimentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The percentage of low attenuation areas/volumes for the total lung areas/volumes on thin-section CT scans are widely known to be significantly correlated with the results of various pulmonary function tests, including spirometry and diffusing capacity of the lungs for carbon monoxide. [4][5][6] Although current quantitative emphysema measurements can be automatically performed by commercially available workstations and open-access software, the measurements are affected by several scanning/reconstruction parameters and other factors, including section thickness, reconstruction kernels, radiation dose settings, iterative reconstruction techniques, and brand of scanner. [4][5][6][7][8][9]12,13 It has been reported that the extent of emphysema tends to increase with thinner sections and sharper reconstruction kernels.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Although current quantitative emphysema measurements can be automatically performed by commercially available workstations and open-access software, the measurements are affected by several scanning/reconstruction parameters and other factors, including section thickness, reconstruction kernels, radiation dose settings, iterative reconstruction techniques, and brand of scanner. [4][5][6][7][8][9]12,13 It has been reported that the extent of emphysema tends to increase with thinner sections and sharper reconstruction kernels. 9 Furthermore, compared with conventional filtered-back-projection (FBP) methods, an iterative reconstruction (IR) algorithm can stabilize emphysema measurements with low-dose settings, and reduce radiation exposure without compromising image quality.…”
Section: Introductionmentioning
confidence: 99%